Faktor Pengasuh dengan Self Esteem (Harga Diri) pada Remaja - Anisa Febristi (Sarana Ilmu Indonesia (salnesia), 2021)
Adolescence is a period of transition from childhood to adulthood, a critical period of changes in the physical period, social problems, and psychological problems. Adolescence is one of the riskiest developmental stages in mental health. One of the psychological problems is low self-esteem. The formation of self-esteem in adolescent orphanages begins with individuals, caregivers, parents, peers, and the environment which will affect individual self-esteem. This study aimed to determine the relationship between caregiver factors and self-esteem. Analytical descriptive research design, cross-sectional study approach. The research location was 30 orphanages in the city of Padang, with a sample of 256 adolescents using a proportional stratified random sampling technique. Data were analyzed using chi-square and logistic regression analysis. The results showed that more than half (52.3%) of adolescents in orphanages experienced negative Self Esteem. There was a relationship between caregiver factors and self-esteem of adolescents in orphanages with p-Value <? (p = 0.005). It is hoped that with the results of this study, the nursing staff can increase the quality and quantity and in nursing practice can increase the knowledge effort for the special youth group program to provide Self Esteem education to adolescents in the orphanage.